Simulasi Pengaruh Jumlah Palang Rim Sepeda Motor Terhadap Equivalent von Mises stress dan Safety Factor Menggunakan Software Ansys - Dwilingga, I.; Sugiman, S.; Catur, A.D. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
Rim or wheels have various types of model designs and the number of spokes. Therefore, those wheels can have a different response on each rim model when subjected to loads such as impact loads. In this simulation, impact load testing is carried out on the rim, with variations of 4 types of geometry where this geometry differs in the design of the number of spokes. By finding the Safety Factor value on each rim,  the most optimal rim design can be determined. Explicit Dynamics can solve this problem because the impact on the simulation occurs in a very short time. In this study, the design of a cast wheel type motorcycle rim with spokes number of 5, 6, 10 and 12 with a uniformly applied impact speed of 10 km/h. The rim material used was aluminum 6061 T6 and the projectile material used was aluminum alloy. The designed rim has a diameter of 35.56 cm and a width of 4.01 cm and a mass of 2415 gram. Solidworks and Ansys software based on the finite element method were used to make it easier to design cast wheel rims. By using this software, the rim can be designed so that it can be analyzed for stresses and strains that occur when simulating impact loads on the rim plane. The simulation results show that rims with spoke 10 and 12 are categorized as safe because they have a lower average stress value than rims 5 and 6 and have a Safety Factor value above 1. In other words, rims with 10 and 12 number of spokes are the optimal design in terms of cost and strength.